2017
DOI: 10.1002/jsfa.8402
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound enhances calcium absorption of jujube fruit by regulating the cellular calcium distribution and metabolism of cell wall polysaccharides

Abstract: These results demonstrated that the combination of CaCl and ultrasound has potential commercial application to extend the shelf life of jujube fruit by facilitating Ca absorption and stabilizing the cell wall structure. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 39 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…Ca 2+ , a universal second messenger, plays an important role in the transduction of growth and development signaling, environmental signaling and hormone signaling (Yang and Poovaiah, 2003 ; Hetherington and Brownlee, 2004 ; Batistič and Kudla, 2012 ). The importance of Ca 2+ for improving or maintaining fruit quality has long been recognized (Oms-Oliu et al, 2010 ; Zhi et al, 2017 ). However, there are relatively few studies on the effects of Ca 2+ on the metabolism of anthocyanins and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ , a universal second messenger, plays an important role in the transduction of growth and development signaling, environmental signaling and hormone signaling (Yang and Poovaiah, 2003 ; Hetherington and Brownlee, 2004 ; Batistič and Kudla, 2012 ). The importance of Ca 2+ for improving or maintaining fruit quality has long been recognized (Oms-Oliu et al, 2010 ; Zhi et al, 2017 ). However, there are relatively few studies on the effects of Ca 2+ on the metabolism of anthocyanins and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…C and D) during the entire storage periods, suggesting that the optimal range of Ca(NO 3 ) 2 concentration application might be between 5 and 10 g L −1 . At this recommended concentration, increased Ca 2+ uptake by the fruit reinforced tissue rigidity . Exceeding the maximum threshold of Ca concentration would result in injury to the fruit surface and deterioration of fruit quality …”
Section: Resultsmentioning
confidence: 99%
“…Postharvest application of Ca in the washing process has been shown to directly improve fruit postharvest quality. The most pronounced and consistent effect of Ca on fruit is to increase fruit Ca uptake and result in firmer fruit with less susceptibility to postharvest disorders . Our previous study indicated that adding 10 g L −1 calcium nitrate (Ca(NO 3 ) 2 ) in SAEW reduced loss in fruit firmness (FF), delayed the disassembly of cell‐wall pectins, and protected fruit antioxidant systems in peach fruit .…”
Section: Introductionmentioning
confidence: 99%
“…Zhi et al. (2017) observed that WSP and CSP contents increased along with the decrease of SSP content due to the implement in polygalacturonase (PG) and pectate lyase (PL) activity during 6 days of storage. Currently, several pre‐harvest and post‐harvest applications have been used to inhibit the softening of jujubes during storage, including physical, chemical and biological methods.…”
Section: Introductionmentioning
confidence: 99%